2020
DOI: 10.1371/journal.pntd.0008180
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and spatial determinants of enteric pathogen infection in rural Lao People’s Democratic Republic: A cross-sectional study

Abstract: Though the health risks associated with poor access to water, sanitation, and hygiene (WASH) are well established, recent large-scale WASH trials have found limited impact on enteric disease. The aims of this study were to: 1. estimate the prevalence of enteropathogens among children <5, school-aged children, and adults; 2. model associations between WASH transmission pathways and enteropathogen infections; and 3. quantify clustering of enteropathogen infections at the household-and village-level. We conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Four studies suggested owning livestock to be a risk factor for infection of CU5 or adults with enteric protozoa or Campylobacter spp. ( 200 , 203 , 206 , 207 ). For families owning livestock, increasing livestock density in/around the households has been associated with visible indoor contamination of animal feces and infection by intestinal parasites (including Giardia lamblia ) in household members ( 210 , 220 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies suggested owning livestock to be a risk factor for infection of CU5 or adults with enteric protozoa or Campylobacter spp. ( 200 , 203 , 206 , 207 ). For families owning livestock, increasing livestock density in/around the households has been associated with visible indoor contamination of animal feces and infection by intestinal parasites (including Giardia lamblia ) in household members ( 210 , 220 ).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies defined the pathogens at the genus level (e.g., Salmonella, Cryptosporidium spp.) (202)(203)(204)(205), and 8 studies characterized pathogens with general biological groups only [i.e., enteric protozoa infection (206,207), intestinal parasite infection (208)(209)(210)(211)(212), enteric pathogen infection (213)]. We therefore defined pathogens as zoonotic (Z) and as zoonotic and/or anthroponotic (A/Z) as in section Enteric pathogens as determinants of EED or undernutrition in children under five.…”
Section: Risks Factors Of Exposure To or Infection With Zoonotic Enteric Pathogens Associated With Smallholder Livestock Productionmentioning
confidence: 99%
“…[ 22 ], which are transmitted from person-to-person via contaminated hands in households. A community-based study involving 1159 households in rural Lao PDR showed that enteropathogen infections are strongly correlated within members of the same household, suggesting the importance of intra-household transmission [ 14 ]. A randomized controlled trial with volunteers in the U.K. showed that hand-washing with plain soap is more effective for the removal of bacterial pathogens from hands than hand-washing with water alone [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, two studies have assessed this association in Lao PDR. A cross-sectional study with 297 households in 50 villages in Saravan province examined associations between the presence of household hand-washing facilities and the infection status of diarrhea-causing pathogens among household members, including children U5 [ 14 ]. The study found that the presence of household hand-washing facilities was associated with lower infection rates of viral enteric pathogens and soil-transmitted helminths among household members.…”
Section: Introductionmentioning
confidence: 99%
“…The morbidity and distribution of diarrhea would be affected by various factors, including sociodemographic factors (age, education, income etc.) [10][11][12], environmental and sanitation factors (poor access to a good water source and poor sanitation) [13,14], and climate factors (rainfall, temperature and humidity) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%